NKG2D as a Cell Surface Marker on γδ-T Cells for Predicting Pregnancy Outcomes in Patients With Unexplained Repeated Implantation Failure - Huang, Chunyu; Xiang, Zheng; Zhang, Yongnu; Li, Yuye; Xu, Jian; Zhang, Hongzhan; Zeng, Yong; Tu, Wenwei (Frontiers in Immunology, 2021)
Maternal immune tolerance to semi-allogeneic fetus is essential for a successful implantation and pregnancy. Growing evidence indicated that low cytotoxic activity of γδ-T cells, which is mediated by activation and inhibitory receptors, is important for establishment of maternal immune tolerant microenvironment. However, the correlation between receptors on peripheral blood γδ-T cells, such as NKG2D, CD158a and CD158b, and pregnancy outcome in patients with unexplained repeated implantation failure (uRIF) remains unclear. In this study, the association between the expression level of these receptors and pregnancy outcome in patients with uRIF was investigated. Thirty-eight women with uRIF were enrolled and divided into two groups： successful group and failed group, according to the pregnancy outcome on different gestational periods. The percentage of NKG2D+ γδ-T cells in lymphocytes was significantly higher in uRIF patients who had failed clinical pregnancy in subsequent cycle, compared with those who had successful clinical pregnancy. However, there were no differences about the frequencies of CD158a+ and CD158b+ γδ-T cells between the successful and failed groups. The receiver operating characteristic curve exhibited that the optimal cut-off value of NKG2D+ γδ-T cells was 3.24%, with 92.3% sensitivity and 66.7% specificity in predicting clinical pregnancy failure in uRIF patients. The patients with uRIF were further divided into two groups, group 1 (NKG2D+ γδ-T cells <3.24%) and group 2 (NKG2D+ γδ-T cells ≥3.24%), based on the cut-off value. The live birth rate of patients in the group 1 and group 2 were 61.5% and 28.0%, respectively. Kaplan-Meier survival curve further suggested that the frequency of NKG2D+ γδ-T cells in lymphocytes negatively correlated with live birth rate in patients with uRIF. In conclusion, our study demonstrated that the frequency of peripheral blood NKG2D+ γδ-T cells among lymphocytes is a potential predictor for pregnancy outcome in uRIF patients.